Selective vitamin D receptor activation with paricalcitol for reduction of albuminuria in patients with type 2 diabetes (VITAL study): a randomised controlled trial - Zeeuw, Dick de; Agarwal, Rajiv; Amdahl, Michael; Audhya, Paul; Coyne, Daniel; Garimella, Tushar; Parving, Hans-Henrik; Pritchett, Yili; Remuzzi, Giuseppe; Ritz, Eberhard; Andress, Dennis (The lancet, 2010)
BACKGROUND: Despite treatment with renin-angiotensin-aldosterone system (RAAS) inhibitors, patients with diabetes have increased risk of progressive renal failure that correlates with albuminuria. We aimed to assess whether paricalcitol could be used to reduce albuminuria in patients with diabetic nephropathy. - METHODS: In this multinational, placebo-controlled, double-blind trial, we enrolled patients with type 2 diabetes and albuminuria who were receiving angiotensin-converting enzyme inhibitors or angiotensin receptor blockers. Patients were assigned (1:1:1) by computer-generated randomisation sequence to receive 24 weeks’ treatment with placebo,1 μg/day paricalcitol, or 2 μg/day paricalcitol. The primary endpoint was the percentage change in geometric mean urinary albumin-to-creatinine ratio (UACR) from baseline to last measurement during treatment for the combined paricalcitol groups versus the placebo group. Analysis was by intention to treat. This trial is registered with ClinicalTrials.gov, number NCT00421733. - FINDINGS: Between February, 2007, and October, 2008, 281 patients were enrolled and assigned to receive placebo(n=93), 1 μg paricalcitol (n=93), or 2 μg paricalcitol (n=95); 88 patients on placebo, 92 on 1 μg paricalcitol, and 92 on2 μg paricalcitol received at least one dose of study drug, and had UACR data at baseline and at least one timepoint during treatment, and so were included in the primary analysis. Change in UACR was: -3% (from 61 to 60 mg/mmol;95% CI -16 to 13) in the placebo group; -16% (from 62 to 51 mg/mmol; -24 to -9) in the combined paricalcitol groups, with a between-group difference versus placebo of -15% (95% CI -28 to 1; p=0.071); -14% (from 63 to 54 mg/mmol; -24 to -1) in the 1 μg paricalcitol group, with a between-group difference versus placebo of -11%(95% CI -27 to 8; p=0.23); and -20% (from 61 to 49 mg/mmol; -30 to -8) in the 2 μg paricalcitol group, with a between-group difference versus placebo of -18% (95% CI -32 to 0; p=0.053). Patients on 2 μg paricalcitol showed a nearly, sustained reduction in UACR, ranging from -18% to -28% (p=0.014 vs placebo). Incidence of hypercalcaemia,adverse events, and serious adverse events was similar between groups receiving paricalcitol versus placebo. - INTERPRETATION: Addition of 2 μg/day paricalcitol to RAAS inhibition safely lowers residual albuminuria in patients with diabetic nephropathy, and could be a novel approach to lower residual renal risk in diabetes. - FUNDING: Abbott.
Gesehen am 10.10.2023